A case-control auditory evaluation of patients treated with artemisinin derivatives for multidrug-resistant Plasmodium falciparum malaria. - Van Vugt, M; Angus, B; Price, R; Mann, C; Simpson, J; Poletto, C; Htoo, SE; Looareesuwan, S; White, N; Nosten, F (2000)
The artemisinin derivatives are now used widely in areas with multidrug-resistant Plasmodium falciparum malaria such as Southeast Asia, but concerns remain over their potential for neurotoxicity. Mice, rats, dogs, and monkeys treated with high doses of intramuscular artemether or arteether develop an unusual pattern of focal damage to brain stem nuclei (particularly those involved in auditory processing). To investigate whether a similar toxic effect occurs in patients treated with these compounds, clinical neurologic evaluation, audiometry and early latency auditory evoked responses were measured in a single-blind comparison of 79 patients who had been treated with > or =2 courses of oral artemether or artesunate within the previous 3 years, and 79 age- and sex-matched controls living in a malaria-endemic area on the northwestern border of Thailand. There were no consistent differences in any of these test results between the cases and controls. This study failed to detect any evidence of significant neurotoxicity in patients treated previously with oral artemether or artesunate for acute malaria.